2003
DOI: 10.1159/000073897
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Treatment of Unruptured Intracranial Aneurysms by Neurosurgical Clipping or by Embolisation with Coils

Abstract: Background: Relatively high rates of complications occur after operation for unruptured intracranial aneurysms. Published data on endovascular treatment suggest lower rates of complications. We measured the impact of treatment of unruptured aneurysms by clipping or coiling on functional health, quality of life, and the level of anxiety and depression. Methods: In three centres, we prospectively collected data on patients with an unruptured aneurysm who were treated by clipping or coiling. Treatment assignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 18 publications
(23 reference statements)
4
62
1
4
Order By: Relevance
“…3,12 For microsurgical treatment, other studies found that clipping of unruptured intracranial aneurysms has a negative impact on health-related quality of life in the first 3 months after treatment, which improves markedly but not completely within 1 year after surgery. 10,13,14 For endovascular treatment, only one study including 19 patients assessed health-related quality of life after treatment of unruptured aneurysms and found no effect.…”
Section: Discussionmentioning
confidence: 99%
“…3,12 For microsurgical treatment, other studies found that clipping of unruptured intracranial aneurysms has a negative impact on health-related quality of life in the first 3 months after treatment, which improves markedly but not completely within 1 year after surgery. 10,13,14 For endovascular treatment, only one study including 19 patients assessed health-related quality of life after treatment of unruptured aneurysms and found no effect.…”
Section: Discussionmentioning
confidence: 99%
“…These have generally indicated that there may be a short-term negative impact on quality of life but largely with full recovery to baseline or to reference population values by 1 to 3 years after treatment. 215,216 In terms of specific complications after UIA surgery, the rate of seizure after craniotomy for UIA is poorly defined. Analyses of administrative data sets have reported a very low incidence of 0.1% for status epilepticus 199 and as high as 9.2% when reporting any seizures, 217 although these studies do not account for preexisting seizures or use of anticonvulsant drugs.…”
Section: Surgical Clipping Outcomesmentioning
confidence: 99%
“…Giant and posterior circulation aneurysms have a higher rate of postoperative complications compared with small anterior circulation aneurysms [60] . In one study, unruptured aneurysm coil embolization was associated with permanent complication rate of 6.7% and 1,4% mortality [58] .…”
Section: T R E a T M E N T O F I N T R A C R A N I A L Aneurysmsmentioning
confidence: 97%
“…Overall risk of death or permanent disability following treatment of ruptured aneurysm is approximately 5%, and for permanent cognitive functions impairment is about 10%. Some authors believe that risk is higher for neurosurgical clipping than endovascular coiling [57,58] . The risk associated with surgery is the higher the larger is the IA diameter, so aneurysms detected during screening procedure as generally smaller are associated with slightly lower risk [59] .…”
Section: T R E a T M E N T O F I N T R A C R A N I A L Aneurysmsmentioning
confidence: 99%